A Glimpse of the Structural Biology of the Metabolism of Sphingosine-1-Phosphate. (February 2021) - Ren, Ruobing; Pang, Bin; Han, Yufei; Li, Yihao
As a key sphingolipid metabolite, sphingosine-1-phosphate (S1P) plays crucial roles in vascular and immune systems. It regulates angiogenesis, vascular integrity and homeostasis, allergic responses, and lymphocyte trafficking. S1P is interconverted with sphingosine, which is also derived from the deacylation of ceramide. S1P levels and the ratio to ceramide in cells are tightly regulated by its metabolic pathways. Abnormal S1P production causes the occurrence and progression of numerous severe diseases, such as metabolic syndrome, cancers, autoimmune disorders such as multiple sclerosis, and kidney and cardiovascular diseases. In recent years, huge advances on the structure of S1P metabolic pathways have been accomplished. In this review, we have got a glimpse of S1P metabolism through structural and biochemical studies of: sphingosine kinases, S1P transporters and S1P receptors, and the development of therapeutics targeting S1P signaling. The progress we summarize here could provide fresh perspectives to further the exploration of S1P functions and facilitate the development of therapeutic molecules targeting S1P signaling with improved specificity and therapeutic effects.